(untitled) (The Planet, 2023)
Introduction: PCOS is a heterogeneous condition affecting7-10% of women worldwide, irrespective of ethnicbackground, making it the most common endocrinedisorder among reproductive-aged women. The 2003Androgen Excess Society (AES) consensus required two ofthe following three criteria as necessary for the diagnosis.This study aimed to analyze the comparison between PCOS& healthy subjects on glycemic & lipid profile status.Methods and materials: This cross-sectional analyticalstudy was carried out in the Department of Obstetrics andGynaecology, Sir Salimullah Medical College & MitfordHospital, Dhaka from September 2019 to August 2020. 80cases were included. A purposive convenient samplingtechnique was undertaken in this study. Result: The studypopulation consisted of 80 individuals, with a mean age ofapproximately 24 years and a mean BMI of around 27. The majority of participants in bothgroups were overweight (58%), while 15% were classified as obese and only 25% fell withinthe normal weight range. The study group had significantly higher fasting blood glucoselevels (4.96 mg/dl) compared to the comparison group (4.42 mg/dl). Additionally, the studygroup exhibited higher triglyceride and total cholesterol levels, along with lower levels ofHDL cholesterol. However, there was no significant difference in LDL cholesterol levels between the PCOS cases and the non-PCOS group. Conclusion: The results of this study showed that women with PCOS had altered lipid profiles and glycemic status. So, it can be concluded thatpoor glycemic control along with deranged lipid profile status predisposes to PCOS.